Formación de un consorcio empresarial para mejorar la estructura de costos de producción de la MYPES del calzado El Porvenir - Trujillo, 2016. - Gavidia Rodriguez, Humberto Percy (2019)
ABSTRACT This research describes the formation of a business consortium to improve the production cost structure of the footwear MyPES of El Porvenir Trujillo 2016. Its general objective was to demonstrate that the formation of a Business Consortium improves th e structure of production costs of the MYPES of the Footwear of the El Porvenir district, being a quantitative method with a population of 733 MyPES and a sample of 252 MyPES. He was a situational diagnosis by identifying existing bottlenecks along the ma nufacturing chain of footwear in the District of El Porvenir and then an analysis of the structure of costs of production of footwear by individual company and Consortium. There has been an analysis of the competitive advantages of associated work to reduc e production costs. Then we designed a model for the formation of a consortium between the producers of footwear, which represent all the interactions of the processes taking place in the company and allow you to meet the commitments. Concluding that produ cers face limitations that restrict their competitiveness and participation in an access value chains to the market, access to training, development of collaboration and coordination between stakeholders and access to financing. The formation of a consorti um would improve cost structure to reduce the cost of labor, raw materials for purchase in larger volumes and ensure presence in the market.